Professional Zakat in Modern Society Life: Provisions Regarding Intellectual Property Objects, Nisab, and Zakat Level - Shabarullah Shabarullah; Fitria Andriani; Muhammad Sufyan Naim bin Shahrinizam (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2021)
Abstract: In the modern era, scholars have determined some of wealth that must be issued zakat beyond what has been stipulated in the text of the Al-Qur'an and as-Sunnah, and one of them is intellectual property. This article examines the opinions and arguments of the scholars regarding the inclusion of intellectual property rights as objects of zakat and both the nisab and zakat levels. This article is based on library data, both primary and secondary. Using a normative and historical approach and by utilizing modern zakat theory, this article concludes that intellectual property is part of wealth, which has both, benefits and economic value. Based on this fact, intellectual property is part of the object of zakat, namely the object of profession zakat. This is based on the general meaning of lafadz infaq in QS. al-Baqarah [2]: verse 267; the generality of the meaning of "wealth" (al-māl) for which zakat is obligatory in QS. at-Taubah [9]: 103, and also the practice of Muslim society in the past. In addition, this article also concludes that the calculation of the nisab for intellectual property is the same as the nisab for agricultural products. In the Indonesian context, it is equivalent to 653 kg of grain. While the level of zakat is the same as the level of gold zakat, which is 2.5%. Thus, this article at the same time proves that Islamic law, especially the teachings on zakat, is not static, but changes and develops according to the dynamics and development of human life.Abstrak: Di era modern, para ulama menetapkan sejumlah harta kekayaan yang wajib dikeluarkan zakatnya di luar apa yang telah ditetapkan dalam nash Al-Qur’an dan as-Sunnah, dan salah satunya adalah kekayaan intelektual. Artikel ini mengkaji pendapat dan argumen para ulama mengenai dimasukkannya hak kekayaan intelektual sebagai objek zakat dan sekaligus penentuan nisab dan kadar zakatnya. Artikel ini didasarkan pada data-data kepustakaan, baik yang bersifat primer maupun sekunder. Menggunakan pendekatan normatif dan historis dan dengan memanfaatkan teori zakat modern, artikel ini menyimpulkan bahwa kekayaan intelektual merupakan bagian dari harta kekayaan, yang memiliki manfaat dan nilai ekonomi sekaligus. Atas dasar kenyataan itulah maka kekayaan intelektual merupakan bagian dari objek zakat, yakni objek zakat profesi. Hal ini didasarkan pada keumuman makna lafadz infaq dalam QS. al-Baqarah [2]: ayat 267; keumuman makna “harta kekayaan” (al-māl) yang wajib dikeluarkan zakatnya dalam QS. at-Taubah [9]: 103, dan juga praktik masyarakat muslim di masa lampau. Selain itu, artikel ini juga menyimpulkan bahwa penghitungan nisab atas kekayaan intelektual adalah sama dengan nisab dari hasil pertanian. Dalam konteks Indonesia, ia sepadan dengan 653 kg gabah. Sedangkan kadar zakatnya adalah sama dengan kadar zakat emas, yakni 2.5%. Dengan demikian, artikel ini sekaligus membuktikan bahwa hukum Islam, khususnya ajaran tentang zakat, tidaklah bersifat statis, tetapi berubah dan berkembang menyesuaikan dinamika dan perkembangan kehidupun manusia.Keywords: Professional zakat; intellectual property rights; objects of Zakat; nisab; zakat level